2012
DOI: 10.1002/icd.1756
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Changes in Visual and Auditory Inhibition in Early Childhood

Abstract: The development of executive functions in the preschool years is not fully understood. Although there exists a large body of research investigating the maturation of executive functioning in school‐aged children, little is known about the emergence of such skills, in particular inhibition, among preschool‐aged children. Understanding developmental changes of inhibition proficiencies and deficiencies early in childhood is important for charting typical and atypical developmental trajectories. Using an adapted c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 47 publications
2
10
0
Order By: Relevance
“…To date, most studies regarding ADHD symptoms in children with FXS are cross sectional (Sullivan et al ; Bailey et al ). Those studies that have longitudinal data and predictive information regarding outcome trajectories often focus on one aspect of ADHD, such as attention (Guy et al ; Scerif et al ; Cornish et al ). Further, longitudinal research temperament has provided information about the stability of temperament characteristics throughout childhood (Rothbart et al ; Putnam et al ), but there is a lack of longitudinal temperament data informing behavioural outcomes in typically developing and special populations of children.…”
Section: Introductionmentioning
confidence: 99%
“…To date, most studies regarding ADHD symptoms in children with FXS are cross sectional (Sullivan et al ; Bailey et al ). Those studies that have longitudinal data and predictive information regarding outcome trajectories often focus on one aspect of ADHD, such as attention (Guy et al ; Scerif et al ; Cornish et al ). Further, longitudinal research temperament has provided information about the stability of temperament characteristics throughout childhood (Rothbart et al ; Putnam et al ), but there is a lack of longitudinal temperament data informing behavioural outcomes in typically developing and special populations of children.…”
Section: Introductionmentioning
confidence: 99%
“…Past research has confirmed the ability of children age 7 years to complete, independently, a seated bimanual task (Roncesvalles et al, 2005) and an auditory Stroop task (Guy et al, 2012) in an accurate and efficient manner similar to that used by adults. It was our goal to combine these tasks to elucidate strategies that children use to attempt motor and cognitive tasks simultaneously, a daily challenge faced by children in this age group.…”
Section: Discussionmentioning
confidence: 90%
“…Based on the rationale of interference, this test asks the subject to identify the pitch (high or low) of the words ''high'' and ''low''; congruent and incongruent auditory cues are randomly issued. The irrelevant dimension (i.e., the word) is processed faster then the relevant dimension (i.e., the pitch) causing interference and increased reaction time for incongruent trials (Guy et al, 2012;Jerger et al, 1988). A cognitive load 'ceiling effect' has been revealed in children 6 years of age using this paradigm.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations